(untitled) (Research, Society and Development, 2021)
Osteoporosis is a serious condition due to the fractures it is responsible for. The frequency of the disease is high and proportional to age. The Brazilian population is aging, therefore, it is increasing. The impact of osteoporosis on the healthcare system will therefore increase. In addition to its effect on the skeleton in general, osteoporosis also has significant consequences for oral health. In fact, it can have an impact: at the level of the teeth, it can cause a gradual loosening of the dentition and the creation of interdental spaces; at the level of the jaw bones, bone loss can make it more difficult to fit dental implants or fit dentures. The aging of the population and the involvement of certain metabolic diseases that affect bone metabolism can interfere with implant placement. Osteoporosis affects bone quality and quantity, so implant placement can be risky. Studies link the loss of dental implants and osteoporosis directly, although they are not statistically significant. Despite the fact that osteoporosis bone quantity and quality are affected, adequate bone formation around the implant and with a similar percentage of bone contact with the implant surface has been demonstrated in healthy individuals versus individuals with osteoporosis.